(* Title: Turing machines
Author: Xu Jian <xujian817@hotmail.com>
Maintainer: Xu Jian
*)
theory turing_basic
imports Main
begin
section {* Basic definitions of Turing machine *}
datatype action = W0 | W1 | L | R | Nop
datatype cell = Bk | Oc
type_synonym tape = "cell list \<times> cell list"
type_synonym state = nat
type_synonym instr = "action \<times> state"
type_synonym tprog = "instr list \<times> nat"
type_synonym config = "state \<times> tape"
fun nth_of where
"nth_of xs i = (if i \<ge> length xs then None
else Some (xs ! i))"
lemma nth_of_map [simp]:
shows "nth_of (map f p) n = (case (nth_of p n) of None \<Rightarrow> None | Some x \<Rightarrow> Some (f x))"
apply(induct p arbitrary: n)
apply(auto)
apply(case_tac n)
apply(auto)
done
fun
fetch :: "instr list \<Rightarrow> state \<Rightarrow> cell \<Rightarrow> instr"
where
"fetch p 0 b = (Nop, 0)"
| "fetch p (Suc s) Bk =
(case nth_of p (2 * s) of
Some i \<Rightarrow> i
| None \<Rightarrow> (Nop, 0))"
|"fetch p (Suc s) Oc =
(case nth_of p ((2 * s) + 1) of
Some i \<Rightarrow> i
| None \<Rightarrow> (Nop, 0))"
lemma fetch_Nil [simp]:
shows "fetch [] s b = (Nop, 0)"
apply(case_tac s)
apply(auto)
apply(case_tac b)
apply(auto)
done
fun
update :: "action \<Rightarrow> tape \<Rightarrow> tape"
where
"update W0 (l, r) = (l, Bk # (tl r))"
| "update W1 (l, r) = (l, Oc # (tl r))"
| "update L (l, r) = (if l = [] then ([], Bk # r) else (tl l, (hd l) # r))"
| "update R (l, r) = (if r = [] then (Bk # l, []) else ((hd r) # l, tl r))"
| "update Nop (l, r) = (l, r)"
abbreviation
"read r == if (r = []) then Bk else hd r"
fun step :: "config \<Rightarrow> tprog \<Rightarrow> config"
where
"step (s, l, r) (p, off) =
(let (a, s') = fetch p (s - off) (read r) in (s', update a (l, r)))"
fun steps :: "config \<Rightarrow> tprog \<Rightarrow> nat \<Rightarrow> config"
where
"steps c p 0 = c" |
"steps c p (Suc n) = steps (step c p) p n"
lemma step_red [simp]:
shows "steps c p (Suc n) = step (steps c p n) p"
by (induct n arbitrary: c) (auto)
lemma steps_add [simp]:
shows "steps c p (m + n) = steps (steps c p m) p n"
by (induct m arbitrary: c) (auto)
fun
tm_wf :: "tprog \<Rightarrow> bool"
where
"tm_wf (p, off) = (length p \<ge> 2 \<and> length p mod 2 = 0 \<and>
(\<forall>(a, s) \<in> set p. s \<le> length p div 2
+ off \<and> s \<ge> off))"
(* FIXME: needed? *)
lemma halt_lemma:
"\<lbrakk>wf LE; \<forall>n. (\<not> P (f n) \<longrightarrow> (f (Suc n), (f n)) \<in> LE)\<rbrakk> \<Longrightarrow> \<exists>n. P (f n)"
by (metis wf_iff_no_infinite_down_chain)
abbreviation exponent :: "'a \<Rightarrow> nat \<Rightarrow> 'a list" ("_ \<up> _" [100, 99] 100)
where "x \<up> n == replicate n x"
consts tape_of :: "'a \<Rightarrow> cell list" ("<_>" 100)
fun tape_of_nat_list :: "nat list \<Rightarrow> cell list"
where
"tape_of_nat_list [] = []" |
"tape_of_nat_list [n] = Oc\<up>(Suc n)" |
"tape_of_nat_list (n#ns) = Oc\<up>(Suc n) @ Bk # (tape_of_nat_list ns)"
defs (overloaded)
tape_of_nl_abv: "<am> \<equiv> tape_of_nat_list am"
tape_of_nat_abv : "<(n::nat)> \<equiv> Oc\<up>(Suc n)"
definition tinres :: "cell list \<Rightarrow> cell list \<Rightarrow> bool"
where
"tinres xs ys = (\<exists>n. xs = ys @ Bk \<up> n \<or> ys = xs @ Bk \<up> n)"
fun
shift :: "instr list \<Rightarrow> nat \<Rightarrow> instr list"
where
"shift p n = (map (\<lambda> (a, s). (a, (if s = 0 then 0 else s + n))) p)"
lemma length_shift [simp]:
"length (shift p n) = length p"
by (simp)
fun
adjust :: "instr list \<Rightarrow> instr list"
where
"adjust p = map (\<lambda> (a, s). (a, if s = 0 then (Suc (length p div 2)) else s)) p"
lemma length_adjust[simp]:
shows "length (adjust p) = length p"
by (induct p) (auto)
fun
tm_comp :: "instr list \<Rightarrow> instr list \<Rightarrow> instr list" ("_ |+| _" [0, 0] 100)
where
"tm_comp p1 p2 = ((adjust p1) @ (shift p2 ((length p1) div 2)))"
fun
is_final :: "config \<Rightarrow> bool"
where
"is_final (s, l, r) = (s = 0)"
lemma is_final_steps:
assumes "is_final (s, l, r)"
shows "is_final (steps (s, l, r) (p, off) n)"
using assms by (induct n) (auto)
fun
holds_for :: "(tape \<Rightarrow> bool) \<Rightarrow> config \<Rightarrow> bool" ("_ holds'_for _" [100, 99] 100)
where
"P holds_for (s, l, r) = P (l, r)"
(*
lemma step_0 [simp]:
shows "step (0, (l, r)) p = (0, (l, r))"
by simp
lemma steps_0 [simp]:
shows "steps (0, (l, r)) p n = (0, (l, r))"
by (induct n) (simp_all)
*)
lemma is_final_holds[simp]:
assumes "is_final c"
shows "Q holds_for (steps c (p, off) n) = Q holds_for c"
using assms
apply(induct n)
apply(case_tac [!] c)
apply(auto)
done
type_synonym assert = "tape \<Rightarrow> bool"
definition assert_imp :: "assert \<Rightarrow> assert \<Rightarrow> bool" ("_ \<mapsto> _" [0, 0] 100)
where
"assert_imp P Q = (\<forall>l r. P (l, r) \<longrightarrow> Q (l, r))"
lemma holds_for_imp:
assumes "P holds_for c"
and "P \<mapsto> Q"
shows "Q holds_for c"
using assms unfolding assert_imp_def by (case_tac c, auto)
lemma test:
assumes "is_final (steps (1, (l, r)) p n1)"
and "is_final (steps (1, (l, r)) p n2)"
shows "Q holds_for (steps (1, (l, r)) p n1) \<longleftrightarrow> Q holds_for (steps (1, (l, r)) p n2)"
proof -
obtain n3 where "n1 = n2 + n3 \<or> n2 = n1 + n3"
by (metis le_iff_add nat_le_linear)
with assms show "Q holds_for (steps (1, (l, r)) p n1) \<longleftrightarrow> Q holds_for (steps (1, (l, r)) p n2)"
by(case_tac p) (auto)
qed
definition
Hoare :: "assert \<Rightarrow> tprog \<Rightarrow> assert \<Rightarrow> bool" ("({(1_)}/ (_)/ {(1_)})" 50)
where
"{P} p {Q} \<equiv>
(\<forall>l r. P (l, r) \<longrightarrow> (\<exists>n. is_final (steps (1, (l, r)) p n) \<and> Q holds_for (steps (1, (l, r)) p n)))"
lemma HoareI:
assumes "\<And>l r. P (l, r) \<Longrightarrow> \<exists>n. is_final (steps (1, (l, r)) p n) \<and> Q holds_for (steps (1, (l, r)) p n)"
shows "{P} p {Q}"
unfolding Hoare_def using assms by auto
text {*
{P1} A {Q1} {P2} B {Q2} Q1 \<mapsto> P2
-----------------------------------
{P1} A |+| B {Q2}
*}
lemma step_0 [simp]:
shows "step (0, (l, r)) p = (0, (l, r))"
by (case_tac p, simp)
lemma steps_0 [simp]:
shows "steps (0, (l, r)) p n = (0, (l, r))"
by (induct n) (simp_all)
declare steps.simps[simp del]
lemma before_final:
assumes "steps (1, tp) A n = (0, tp')"
obtains n' where "\<not> is_final (steps (1, tp) A n')"
and "steps (1, tp) A (Suc n') = (0, tp')"
proof -
from assms have "\<exists> n'. \<not> is_final (steps (1, tp) A n') \<and>
steps (1, tp) A (Suc n') = (0, tp')"
proof(induct n arbitrary: tp', simp add: steps.simps)
fix n tp'
assume ind:
"\<And>tp'. steps (1, tp) A n = (0, tp') \<Longrightarrow>
\<exists>n'. \<not> is_final (steps (1, tp) A n') \<and> steps (1, tp) A (Suc n') = (0, tp')"
and h: " steps (1, tp) A (Suc n) = (0, tp')"
from h show "\<exists>n'. \<not> is_final (steps (1, tp) A n') \<and> steps (1, tp) A (Suc n') = (0, tp')"
proof(simp add: step_red del: steps.simps,
case_tac "(steps (Suc 0, tp) A n)", case_tac "a = 0", simp)
fix a b c
assume " steps (Suc 0, tp) A n = (0, tp')"
hence "\<exists>n'. \<not> is_final (steps (1, tp) A n') \<and> steps (1, tp) A (Suc n') = (0, tp')"
apply(rule_tac ind, simp)
done
thus "\<exists>n'. \<not> is_final (steps (Suc 0, tp) A n') \<and> step (steps (Suc 0, tp) A n') A = (0, tp')"
apply(simp)
done
next
fix a b c
assume "steps (Suc 0, tp) A n = (a, b, c)"
"step (steps (Suc 0, tp) A n) A = (0, tp')"
"a \<noteq> 0"
thus "\<exists>n'. \<not> is_final (steps (Suc 0, tp) A n') \<and>
step (steps (Suc 0, tp) A n') A = (0, tp')"
apply(rule_tac x = n in exI, simp)
done
qed
qed
thus "(\<And>n'. \<lbrakk>\<not> is_final (steps (1, tp) A n');
steps (1, tp) A (Suc n') = (0, tp')\<rbrakk> \<Longrightarrow> thesis) \<Longrightarrow> thesis"
by auto
qed
declare tm_comp.simps [simp del] adjust.simps[simp del] shift.simps[simp del]
lemma length_comp:
"length (A |+| B) = length A + length B"
apply(auto simp: tm_comp.simps)
done
lemma tmcomp_fetch_in_first:
assumes "case (fetch A a x) of (ac, ns) \<Rightarrow> ns \<noteq> 0"
shows "fetch (A |+| B) a x = fetch A a x"
using assms
apply(case_tac a, case_tac [!] x,
auto simp: length_comp tm_comp.simps length_adjust nth_append)
apply(simp_all add: adjust.simps)
done
lemma is_final_eq: "is_final (ba, tp) = (ba = 0)"
apply(case_tac tp, simp add: is_final.simps)
done
lemma t_merge_pre_eq_step:
assumes step: "step (a, b, c) (A, 0) = cf"
and tm_wf: "tm_wf (A, 0)"
and unfinal: "\<not> is_final cf"
shows "step (a, b, c) (A |+| B, 0) = cf"
proof -
have "fetch (A |+| B) a (read c) = fetch A a (read c)"
proof(rule_tac tmcomp_fetch_in_first)
from step and unfinal show "case fetch A a (read c) of (ac, ns) \<Rightarrow> ns \<noteq> 0"
apply(auto simp: is_final.simps)
apply(case_tac "fetch A a (read c)", simp_all add: is_final_eq)
done
qed
thus "?thesis"
using step
apply(auto simp: step.simps is_final.simps)
done
qed
declare tm_wf.simps[simp del] step.simps[simp del]
lemma t_merge_pre_eq:
"\<lbrakk>steps (Suc 0, tp) (A, 0) stp = cf; \<not> is_final cf; tm_wf (A, 0)\<rbrakk>
\<Longrightarrow> steps (Suc 0, tp) (A |+| B, 0) stp = cf"
proof(induct stp arbitrary: cf, simp add: steps.simps)
fix stp cf
assume ind: "\<And>cf. \<lbrakk>steps (Suc 0, tp) (A, 0) stp = cf; \<not> is_final cf; tm_wf (A, 0)\<rbrakk>
\<Longrightarrow> steps (Suc 0, tp) (A |+| B, 0) stp = cf"
and h: "steps (Suc 0, tp) (A, 0) (Suc stp) = cf"
"\<not> is_final cf" "tm_wf (A, 0)"
from h show "steps (Suc 0, tp) (A |+| B, 0) (Suc stp) = cf"
proof(simp add: step_red, case_tac "(steps (Suc 0, tp) (A, 0) stp)", simp)
fix a b c
assume g: "steps (Suc 0, tp) (A, 0) stp = (a, b, c)"
"step (a, b, c) (A, 0) = cf"
have "(steps (Suc 0, tp) (A |+| B, 0) stp) = (a, b, c)"
proof(rule ind, simp_all add: h g)
show "0 < a"
using g h
apply(simp add: step_red)
apply(case_tac a, auto simp: step_0)
apply(case_tac "steps (Suc 0, tp) (A, 0) stp", simp)
done
qed
thus "step (steps (Suc 0, tp) (A |+| B, 0) stp) (A |+| B, 0) = cf"
apply(simp)
apply(rule_tac t_merge_pre_eq_step, simp_all add: g h)
done
qed
qed
lemma tmcomp_fetch_in_first2:
assumes "fetch A a x = (ac, 0)"
"tm_wf (A, 0)"
"a \<le> length A div 2" "a > 0"
shows "fetch (A |+| B) a x = (ac, Suc (length A div 2))"
using assms
apply(case_tac a, case_tac [!] x,
auto simp: length_comp tm_comp.simps length_adjust nth_append)
apply(simp_all add: adjust.simps)
done
lemma tmcomp_exec_after_first:
"\<lbrakk>0 < a; step (a, b, c) (A, 0) = (0, tp'); tm_wf (A, 0);
a \<le> length A div 2\<rbrakk>
\<Longrightarrow> step (a, b, c) (A |+| B, 0) = (Suc (length A div 2), tp')"
apply(simp add: step.simps, auto)
apply(case_tac "fetch A a Bk", simp add: tmcomp_fetch_in_first2)
apply(case_tac "fetch A a (hd c)", simp add: tmcomp_fetch_in_first2)
done
lemma step_nothalt_pre: "\<lbrakk>step (aa, ba, ca) (A, 0) = (a, b, c); 0 < a\<rbrakk> \<Longrightarrow> 0 < aa"
apply(case_tac "aa = 0", simp add: step_0, simp)
done
lemma nth_in_set:
"\<lbrakk> A ! i = x; i < length A\<rbrakk> \<Longrightarrow> x \<in> set A"
by auto
lemma step_nothalt:
"\<lbrakk>step (aa, ba, ca) (A, 0) = (a, b, c); 0 < a; tm_wf (A, 0)\<rbrakk> \<Longrightarrow>
a \<le> length A div 2"
apply(simp add: step.simps)
apply(case_tac aa, case_tac [!] aa, auto split: if_splits simp: tm_wf.simps)
apply(case_tac "A ! (2 * nat)", simp)
apply(erule_tac x = "(aa, a)" in ballE, simp_all add: nth_in_set)
apply(case_tac "hd ca", auto split: if_splits simp: tm_wf.simps)
apply(case_tac "A ! (2 * nat)", simp)
apply(erule_tac x = "(aa, a)" in ballE, simp_all add: nth_in_set)
apply(case_tac "A ! (Suc (2 * nat))")
apply(erule_tac x = "(aa,bb)" in ballE, simp_all add: nth_in_set)
done
lemma steps_in_range:
" \<lbrakk>0 < a; steps (Suc 0, tp) (A, 0) stp = (a, b, c); tm_wf (A, 0)\<rbrakk>
\<Longrightarrow> a \<le> length A div 2"
proof(induct stp arbitrary: a b c)
fix a b c
assume h: "0 < a" "steps (Suc 0, tp) (A, 0) 0 = (a, b, c)"
"tm_wf (A, 0)"
thus "a \<le> length A div 2"
apply(simp add: steps.simps tm_wf.simps, auto)
done
next
fix stp a b c
assume ind: "\<And>a b c. \<lbrakk>0 < a; steps (Suc 0, tp) (A, 0) stp = (a, b, c);
tm_wf (A, 0)\<rbrakk> \<Longrightarrow> a \<le> length A div 2"
and h: "0 < a" "steps (Suc 0, tp) (A, 0) (Suc stp) = (a, b, c)" "tm_wf (A, 0)"
from h show "a \<le> length A div 2"
proof(simp add: step_red, case_tac "(steps (Suc 0, tp) (A, 0) stp)", simp)
fix aa ba ca
assume g: "step (aa, ba, ca) (A, 0) = (a, b, c)"
"steps (Suc 0, tp) (A, 0) stp = (aa, ba, ca)"
hence "aa \<le> length A div 2"
apply(rule_tac ind, auto simp: h step_nothalt_pre)
done
thus "?thesis"
using g h
apply(rule_tac step_nothalt, auto)
done
qed
qed
lemma t_merge_pre_halt_same:
assumes a_ht: "steps (1, tp) (A, 0) n = (0, tp')"
and a_wf: "tm_wf (A, 0)"
obtains n' where "steps (1, tp) (A |+| B, 0) n' = (Suc (length A div 2), tp')"
proof -
assume a: "\<And>n. steps (1, tp) (A |+| B, 0) n = (Suc (length A div 2), tp') \<Longrightarrow> thesis"
obtain stp' where "\<not> is_final (steps (1, tp) (A, 0) stp')" and
"steps (1, tp) (A, 0) (Suc stp') = (0, tp')"
using a_ht before_final by blast
then have "steps (1, tp) (A |+| B, 0) (Suc stp') = (Suc (length A div 2), tp')"
proof(simp add: step_red)
assume "\<not> is_final (steps (Suc 0, tp) (A, 0) stp')"
" step (steps (Suc 0, tp) (A, 0) stp') (A, 0) = (0, tp')"
moreover hence "(steps (Suc 0, tp) (A |+| B, 0) stp') = (steps (Suc 0, tp) (A, 0) stp')"
apply(rule_tac t_merge_pre_eq)
apply(simp_all add: a_wf a_ht)
done
ultimately show "step (steps (Suc 0, tp) (A |+| B, 0) stp') (A |+| B, 0) = (Suc (length A div 2), tp')"
apply(case_tac " steps (Suc 0, tp) (A, 0) stp'", simp)
apply(rule tmcomp_exec_after_first, simp_all add: a_wf)
apply(erule_tac steps_in_range, auto simp: a_wf)
done
qed
with a show thesis by blast
qed
lemma tm_comp_fetch_second_zero:
"\<lbrakk>fetch B sa' x = (a, 0); tm_wf (A, 0); tm_wf (B, 0); sa' > 0\<rbrakk>
\<Longrightarrow> fetch (A |+| B) (sa' + (length A div 2)) x = (a, 0)"
apply(case_tac x)
apply(case_tac [!] sa',
auto simp: fetch.simps length_comp length_adjust nth_append tm_comp.simps
tm_wf.simps shift.simps split: if_splits)
done
lemma tm_comp_fetch_second_inst:
"\<lbrakk>sa > 0; s > 0; tm_wf (A, 0); tm_wf (B, 0); fetch B sa x = (a, s)\<rbrakk>
\<Longrightarrow> fetch (A |+| B) (sa + length A div 2) x = (a, s + length A div 2)"
apply(case_tac x)
apply(case_tac [!] sa,
auto simp: fetch.simps length_comp length_adjust nth_append tm_comp.simps
tm_wf.simps shift.simps split: if_splits)
done
lemma t_merge_second_same:
assumes a_wf: "tm_wf (A, 0)"
and b_wf: "tm_wf (B, 0)"
and steps: "steps (Suc 0, l, r) (B, 0) stp = (s, l', r')"
shows "steps (Suc (length A div 2), l, r) (A |+| B, 0) stp
= (if s = 0 then 0
else s + length A div 2, l', r')"
using a_wf b_wf steps
proof(induct stp arbitrary: s l' r', simp add: steps.simps, simp)
fix stpa sa l'a r'a
assume ind: "\<And>s l' r'. steps (Suc 0, l, r) (B, 0) stpa = (s, l', r') \<Longrightarrow>
steps (Suc (length A div 2), l, r) (A |+| B, 0) stpa =
(if s = 0 then 0 else s + length A div 2, l', r')"
and h: "step (steps (Suc 0, l, r) (B, 0) stpa) (B, 0) = (sa, l'a, r'a)"
obtain sa' l'' r'' where a: "(steps (Suc 0, l, r) (B, 0) stpa) = (sa', l'', r'')"
apply(case_tac "steps (Suc 0, l, r) (B, 0) stpa", auto)
done
from this have b: "steps (Suc (length A div 2), l, r) (A |+| B, 0) stpa =
(if sa' = 0 then 0 else sa' + length A div 2, l'', r'')"
apply(erule_tac ind)
done
from a b h show
"(sa = 0 \<longrightarrow> step (steps (Suc (length A div 2), l, r) (A |+| B, 0) stpa) (A |+| B, 0) = (0, l'a, r'a)) \<and>
(0 < sa \<longrightarrow> step (steps (Suc (length A div 2), l, r) (A |+| B, 0) stpa) (A |+| B, 0) = (sa + length A div 2, l'a, r'a))"
proof(case_tac "sa' = 0", auto)
assume "step (sa', l'', r'') (B, 0) = (0, l'a, r'a)" "0 < sa'"
thus "step (sa' + length A div 2, l'', r'') (A |+| B, 0) = (0, l'a, r'a)"
using a_wf b_wf
apply(simp add: step.simps)
apply(case_tac "fetch B sa' (read r'')", auto)
apply(simp_all add: step.simps tm_comp_fetch_second_zero)
done
next
assume "step (sa', l'', r'') (B, 0) = (sa, l'a, r'a)" "0 < sa'" "0 < sa"
thus "step (sa' + length A div 2, l'', r'') (A |+| B, 0) = (sa + length A div 2, l'a, r'a)"
using a_wf b_wf
apply(simp add: step.simps)
apply(case_tac "fetch B sa' (read r'')", auto)
apply(simp_all add: step.simps tm_comp_fetch_second_inst)
done
qed
qed
lemma t_merge_second_halt_same:
"\<lbrakk>tm_wf (A, 0); tm_wf (B, 0);
steps (1, l, r) (B, 0) stp = (0, l', r')\<rbrakk>
\<Longrightarrow> steps (Suc (length A div 2), l, r) (A |+| B, 0) stp
= (0, l', r')"
using t_merge_second_same[where s = "0"]
apply(auto)
done
lemma Hoare_plus_halt:
assumes aimpb: "Q1 \<mapsto> P2"
and A_wf : "tm_wf (A, 0)"
and B_wf : "tm_wf (B, 0)"
and A_halt : "{P1} (A, 0) {Q1}"
and B_halt : "{P2} (B, 0) {Q2}"
shows "{P1} (A |+| B, 0) {Q2}"
proof(rule HoareI)
fix l r
assume h: "P1 (l, r)"
then obtain n1 where a: "is_final (steps (1, l, r) (A, 0) n1)" and b: "Q1 holds_for (steps (1, l, r) (A, 0) n1)"
using A_halt unfolding Hoare_def by auto
then obtain l' r' where "steps (1, l, r) (A, 0) n1 = (0, l', r')" and c: "Q1 holds_for (0, l', r')"
by(case_tac "steps (1, l, r) (A, 0) n1", auto)
then obtain stpa where d: "steps (1, l, r) (A |+| B, 0) stpa = (Suc (length A div 2), l', r')"
using A_wf
by(rule_tac t_merge_pre_halt_same, auto)
from c aimpb have "P2 holds_for (0, l', r')"
by(rule holds_for_imp)
from this have "P2 (l', r')" by auto
from this obtain n2 where e: "is_final (steps (1, l', r') (B, 0) n2)" and f: "Q2 holds_for (steps (1, l', r') (B, 0) n2)"
using B_halt unfolding Hoare_def
by auto
then obtain l'' r'' where "steps (1, l', r') (B, 0) n2 = (0, l'', r'')" and g: "Q2 holds_for (0, l'', r'')"
by(case_tac "steps (1, l', r') (B, 0) n2", auto)
from this have "steps (Suc (length A div 2), l', r') (A |+| B, 0) n2
= (0, l'', r'')"
apply(rule_tac t_merge_second_halt_same, auto simp: A_wf B_wf)
done
thus "\<exists>n. is_final (steps (1, l, r) (A |+| B, 0) n) \<and> Q2 holds_for (steps (1, l, r) (A |+| B, 0) n)"
using d g
apply(rule_tac x = "stpa + n2" in exI)
apply(simp add: steps_add)
done
qed
definition
Hoare_unhalt :: "assert \<Rightarrow> tprog \<Rightarrow> bool" ("({(1_)}/ (_))" 50)
where
"{P} p \<equiv>
(\<forall>l r. P (l, r) \<longrightarrow> (\<forall> n . \<not> (is_final (steps (1, (l, r)) p n))))"
lemma Hoare_unhalt_I:
assumes "\<And>l r. P (l, r) \<Longrightarrow> \<forall> n. \<not> is_final (steps (1, (l, r)) p n)"
shows "{P} p"
unfolding Hoare_unhalt_def using assms by auto
lemma Hoare_plus_unhalt:
assumes aimpb: "Q1 \<mapsto> P2"
and A_wf : "tm_wf (A, 0)"
and B_wf : "tm_wf (B, 0)"
and A_halt : "{P1} (A, 0) {Q1}"
and B_uhalt : "{P2} (B, 0)"
shows "{P1} (A |+| B, 0)"
proof(rule_tac Hoare_unhalt_I)
fix l r
assume h: "P1 (l, r)"
then obtain n1 where a: "is_final (steps (1, l, r) (A, 0) n1)" and b: "Q1 holds_for (steps (1, l, r) (A, 0) n1)"
using A_halt unfolding Hoare_def by auto
then obtain l' r' where "steps (1, l, r) (A, 0) n1 = (0, l', r')" and c: "Q1 holds_for (0, l', r')"
by(case_tac "steps (1, l, r) (A, 0) n1", auto)
then obtain stpa where d: "steps (1, l, r) (A |+| B, 0) stpa = (Suc (length A div 2), l', r')"
using A_wf
by(rule_tac t_merge_pre_halt_same, auto)
from c aimpb have "P2 holds_for (0, l', r')"
by(rule holds_for_imp)
from this have "P2 (l', r')" by auto
from this have e: "\<forall> n. \<not> is_final (steps (Suc 0, l', r') (B, 0) n) "
using B_uhalt unfolding Hoare_unhalt_def
by auto
from e show "\<forall>n. \<not> is_final (steps (1, l, r) (A |+| B, 0) n)"
proof(rule_tac allI, case_tac "n > stpa")
fix n
assume h2: "stpa < n"
hence "\<not> is_final (steps (Suc 0, l', r') (B, 0) (n - stpa))"
using e
apply(erule_tac x = "n - stpa" in allE) by simp
then obtain s'' l'' r'' where f: "steps (Suc 0, l', r') (B, 0) (n - stpa) = (s'', l'', r'')" and g: "s'' \<noteq> 0"
apply(case_tac "steps (Suc 0, l', r') (B, 0) (n - stpa)", auto)
done
have k: "steps (Suc (length A div 2), l', r') (A |+| B, 0) (n - stpa) = (s''+ length A div 2, l'', r'') "
using A_wf B_wf f g
apply(drule_tac t_merge_second_same, auto)
done
show "\<not> is_final (steps (1, l, r) (A |+| B, 0) n)"
proof -
have "\<not> is_final (steps (1, l, r) (A |+| B, 0) (stpa + (n - stpa)))"
using d k A_wf
apply(simp only: steps_add d, simp add: tm_wf.simps)
done
thus "\<not> is_final (steps (1, l, r) (A |+| B, 0) n)"
using h2 by simp
qed
next
fix n
assume h2: "\<not> stpa < n"
with d show "\<not> is_final (steps (1, l, r) (A |+| B, 0) n)"
apply(auto)
apply(subgoal_tac "\<exists> d. stpa = n + d", auto)
apply(case_tac "(steps (Suc 0, l, r) (A |+| B, 0) n)", simp)
apply(rule_tac x = "stpa - n" in exI, simp)
done
qed
qed
end